Prevalence of hepatitis B virus core antibodies among blood donors in Nigeria: implications for blood safety (2022)
Background: Anti-hepatitis B core antibody (anti-HBc) testing improves transfusion safety by detecting past and current hepatitis B virus (HBV) infection while detecting hepatitis B surface antigen (HBsAg) in serology-negative HBV infection. However, occult HBV infection (OBI) (serum or liver HBV DNA-positive but HBsAg-negative) remains unaddressed among replacement blood donors – family members or friends who donate to replace blood transfused to a relative. Objective: This study assessed risk factors for a positive anti-HBc test among donors with OBI and determined the anti-HBc-positive status of replacement donors. Methods: The study was conducted at the University College Hospital Blood Bank, Ibadan, Nigeria, using blood samples collected from blood donors between April 2019 and May 2019. Donors were screened for HBsAg by rapid diagnostic test (RDT) and enzyme-linked immunosorbent assay (ELISA) and anti-HBc by ELISA, while HBV DNA was detected using a semi-nested polymerase chain reaction. Results: Of the 274 participants, 15 (5.5%) were HBsAg-positive by RDT and 36 (13.1%) by ELISA, while 133 (48.5%) were anti-HBc positive. Out of 232 HBsAg-negative donors, 107 (46.1%) were anti-HBc positive. Of the 107 HBsAg-negative but anti-HBc-positive samples, only one (0.93%) was HBV DNA-positive. The HBV DNA-positive donor was HBsAg-negative by both RDT and ELISA tests. Conclusion: This study establishes a potential risk for HBV transmission from isolated anti-HBc-positive donors to blood recipients. HBc immunoglobulin (antibody) M testing to identify blood units requiring further screening with polymerase chain reaction to detect OBI can prevent HBV transmission through blood transfusion.